THE RELATIONSHIP BETWEEN IMPORT TARIFF AND IMPORT ALCOHOL IN THAILAND - Puntngam, Kanokwan; Chanagul, Asst. Prof. Dr.Chittawan (Journal of Buddhist Education and Research (JBER), 2021)
The research objectives were to study the relationship between import tariff and import alcohol in Thailand Case studies yearly and quarterly. The data were collected from Thai customs and analyzed by using descriptive method: import tariff and import alcohol and analyzed by using quantitative method: Time series data were used to test the stationary of the data by Panel unit root test, and long-term equilibrium relationships were tested by the Panel Cointegration Test, and finally, the Granger Causality Test. The results showed that both the annual and quarterly cases Panel Cointegration Test and Granger Causality Test had the same results is in the acceptance of the main hypothesis the data does not cointegration. ie import tariffs and alcohol import in Thailand. There is no long-term equilibrium relationship. however, the results of the causal testing showed that the import tariffs and the alcohol imports are in one way direction.